Comprehensive Analysis of m6A RNA Methylation Regulators in the Prognosis and Immune Microenvironment of Multiple Myeloma - Liu, Rui; Shen, Ying; Hu, Jinsong; Wang, Xiaman; Wu, Dong; Zhai, Meng; Bai, Ju; He, Aili (Frontiers in Oncology, 2021)
Introduction: N6-methyladenosine is the most abundant RNA modification, which plays a prominent role in various biology processes, including tumorigenesis and immune regulation. Multiple myeloma (MM) is the second most frequent hematological malignancy. Materials and Methods: Twenty-two m6A RNA methylation regulators were analyzed between MM patients and normal samples. Kaplan-Meier survival analysis and LASSO Cox regression analysis were employed to construct the risk signature model. Receiver operation characteristic (ROC) curves were used to verify the prognostic and diagnostic efficiency. Immune infiltration level was evaluated by ESTIMATE algorithm and immune-related ssGSEA. Results: High expression of HNRNPC, HNRNPA2B1, YTHDF2 and low expression of ZC3H13 were associated with poor survival. Based on these four genes, a prognostic risk signature model was established. Multivariate Cox regression analysis demonstrated that the risk score was an independent prognostic factor of MM. Enrichment analysis showed that cell cycle, immune response, MYC, proteasome and unfold protein reaction were enriched in high-risk MM patients. Furthermore, patients with higher risk score exhibited lower immune scores and lower immune infiltration level. Conclusion: The m6A-based prognostic risk score accurately and robustly predicts the survival of MM patients, and is associated with the immune infiltration level, which complements current prediction models and enhances our cognition of immune infiltration to improve immunotherapy strategies.